Arthralgia among women taking aromatase inhibitors: is there a shared inflammatory mechanism with co-morbid fatigue and insomnia? - Bauml, Joshua (Breast Cancer Res, 2015)
INTRODUCTION: Arthralgia is a common toxicity among women taking aromatase inhibitors (AIs) and can lead to premature discontinuation of therapy. We evaluated the association between arthralgia, co-morbid fatigue and/or insomnia, and inflammatory biomarkers among women taking AIs. METHODS: Women taking AIs for early-stage breast cancer completed a modified version of the Brief Pain Inventory, the Brief Fatigue Inventory, and the Insomnia Severity Index and provided blood samples for simultaneous assessment of 34 inflammatory biomarkers with a Luminex kit. Two-sided t tests were used to compare inflammatory biomarker concentrations for patients with or without moderate to severe arthralgia. Multivariate linear regression analyses were performed to evaluate the relationship between comorbid arthralgia, fatigue, and insomnia with identified biomarker concentrations. RESULTS: Among 203 participants, the severity of arthralgia, fatigue, and insomnia were significantly correlated with each other (p < 0.001 for all comparisons). After controlling for race, chemotherapy history, non-steroidal anti-inflammatory drug use, age, and body mass index, the coexistence of arthralgia, fatigue, and insomnia was associated with elevated C-reactive protein (CRP) (β = 93.1; 95 % confidence interval (CI): 25.1–161.1; p = 0.008), eotaxin (β = 79.9; 95 % CI: 32.5–127.2; p = 0.001), monocyte chemoattractant protein (MCP)-1 (β = 151.2; 95 % CI: 32.7–269.8; p = 0.013), and vitamin D–binding protein (VDBP) (β = 19,422; 95 % CI: 5500.5–33,344; p = 0.006). CONCLUSIONS: Among women taking AIs, the coexistence of arthralgia, fatigue, and insomnia was associated with increased levels of inflammatory biomarkers (elevated CRP, eotaxin, MCP-1, and VDBP). These findings suggest a possible shared inflammatory mechanism underlying these common symptoms. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13058-015-0599-7) contains supplementary material, which is available to authorized users.